(untitled) (Research, Society and Development, 2019)
This study aimed to obtain more uniform ripening of the fruits harvested by applying growth regulators Ethephon and Mathury™, aimed at improving the quality of coffee drinks. Was used to cultivate Tupi Yellow (IAC 5162), planted in December 2008. The experimental design was a randomized blocks, being employed five treatments: T1 Application Mathury™ to 113 days prior to collection (DAC); T2 Application Mathury™ after 85 DAC; T3 Application Mathury™ after 57 DAC; T4 Ethephon application when the plants were 30% of cherry fruit and T5- Control (without applications). After sorting the fruit maturation percentage, we selected those who were classified as cherry; these were dried and submitted to analysis: selection by size; classification by type of defects; sugars; solid soluble; electrical conductivity; potassium leaching; titratable acidity; ether extract; pH and sensory analysis. There was a significant difference in the ripening of fruits, noting an increase of 57% the percentage of cherry fruit and 89% reduction of fruit goes through when applied Ethephon. While there have been differences in the percentage of fruit maturation and the physical-chemical analysis, it is concluded that such differences did not influence the coffee beverage quality as it achieved the same standard classification panel test.